Experimental study on regeneration performance and particle emission characteristics of DPF with different inlet transition sections lengths. (15th February 2020) - Meng, Zhongwei; Li, Jiansong; Fang, Jia; Tan, Jie; Qin, Yuan; Jiang, Yuan; Qin, Zihan; Bai, Weilian; Liang, Kun
Abstract: In order to efficiently control and optimize the diesel particulate filter (DPF) for internal combustion engines, it is necessary to have a thorough understanding of its regeneration performance and particle emission characteristics. A particle loading system and a DPF regeneration test benches are built to investigate the impact of inlet transition section length ( L T ) of particle loading system on the DPF regeneration process. Five different transition lengths which lead to different particle distributions inside DPF are tested as well as the different regeneration performance and particle emission characteristics. The maximum temperature peaks during regeneration process are found when L T is below 40 cm, while they disappear when L T is 40 cm or 50 cm. The longer the L T is, the more uniform the particle deposition is obtained. The 2500 s, 1500 s and 1000 s are the transition time values for 525 °C, 550 °C and 575 °C when L T is 50 cm, respectively. Before this transition value, it is economical to prolong the regeneration time to promote regeneration efficiency. During the heating up stage, the emitted particle concentration peaks are observed with the concentration increasing by 1–2 orders of magnitude for both 0 cm and 50 cm transaction lengths. During the regeneration stage, the maximum temperature peaks (hot spot) appears and the emitted particle concentration increases by 2–3 orders of magnitude. The mean particle diameter rises from 10 to 20 nm to 300 nm when the L T is 0 cm. The mean diameter about 20 nm is observed when the L T is 50 cm. The results from this study can be used to lay a foundation for optimizing DPF system structure and controlling DPF outlet particle emission.